PSMA-guided management of recurrent post-prostatectomy patients: a sub-analysis of a prospective single-center study - Iorio, Giuseppe Carlo; Grossi, Cristiano; Chiofalo, Valeria; Richetto, Veronica; Rovera, Guido; Bongiovanni, Diego; Parise, Ramona; Clot, Francesca; Oderda, Marco; Grimaldi, Serena; Cuffini, Erica Maria; Levis, Mario; et al. (Frontiers in Oncology, 2026)
IntroductionThe advent of prostate-specific membrane antigen - positron emission tomography (PSMA-PET) imaging influences prostate cancer (PCa) salvage radiotherapy (SRT) decision-making, especially in biochemical recurrence (BCR) with low PSA. This study evaluates the impact of PSMA-PET on recurrent post-prostatectomy patients treated with radiotherapy (RT) ± hormonal therapy (HT).Materials and methodsIn a prospective, observational study (2016–2020), 103 hormone-sensitive post-prostatectomy pN0-pNx PCa patients with proven BCR were analyzed. PSMA-positive patients received tailored treatments based on lesion sites, ranging from prostate bed (P-bed) SRT abort, metastases-directed therapy, to systemic therapy. PSMA-negative patients were mainly treated with SRT. Primary objectives included PSMA-based management changes and biochemical progression-free survival (bPFS) comparison.ResultsPSMA-PET was positive in 28.1% (29/103) at a median PSA of 0.5 ng/mL. The most common relapse sites were bones and pelvic lymph nodes. Among positive PSMA-PET patients, the P-bed abort rate was 58.6% (17/29 patients). Excluding patients with PSMA-positive uptake solely in the P-bed (7 patients), the rate of P-bed abort was 77.3% (17/22 patients). Management was altered in 75.8% of PSMA-positive and 21.3% overall. Most PSMA-positive lesions were managed with SBRT, either as a standalone treatment or within combined-modality approaches: SBRT was delivered to 50% of nodal recurrences (including both N1 and M1a cases) and to 100% of bone lesions. At 5 years, bPFS was 66.8% in PSMA-negative patients (undergoing SRT+/-HT) vs. 26.7% in PSMA-positive patients (any treatment).ConclusionPSMA-PET led to management changes in nearly one-third of post-prostatectomy recurrent PCa, notably affecting RT strategies and systemic therapy. Emerging evidence suggests that treatment intensification based on PSMA-PET findings may improve patient outcomes compared to de-intensified approaches. The impact on outcomes awaits validation from ongoing prospective randomized trials.